Design and techno-economic optimization of a stand-alone PV (photovoltaic)/FC (fuel cell)/battery hybrid power system connected to a wastewater-to-hydrogen processor - Wu, Wei; Christiana, Veni Indah; Chen, Shin-An; Hwang, Jenn-Jiang (Energy (Oxford), 2015)
A wastewater treatment process is developed as a heat-integrated fuel processor to produce hydrogen. If the hydrogen flow is directly connected to the PEMFC (proton exchange membrane fuel cell), then a stand-alone PV/FC/battery hybrid power system is developed to meet the daily load demand. According to the prescribed scenarios such as wastewater conditions and weather patterns, the reliability of the power supply is expressed in terms of the LPSP (loss of power supply probability). To address the lowest cost of electricity, an economic sizing model with regard to the LCE (levelized cost of energy) is taken into account. Regarding the trade-off between investment costs and power reliability, the techno-economic optimization algorithm for the minimization of the LCE subject to LPSP is used to determine the optimum hybrid power system configuration. •A wastewater treatment process is developed as a heat-integrated fuel processor to produce hydrogen.•The performance of the HPG (Hybrid power generation) system is evaluated on the basis of reliability of the power supply.•The optimization of the system size is subsequently predicted on the minimum LCE (levelized cost of energy).•An optimal compromise between investment costs and power reliability is investigated.